Presence of pesticides in surface water from four sub-basins in Argentina - De Geronimo, Eduardo; Aparicio, Virginia Carolina; Barbaro, Sebastian Ernesto; Portocarrero, Rocio; Jaime, Sebastián Andrés; Costa, Jose Luis (Elsevier, 2019)
Argentina has 31 million hectares given over to agriculture comprising 2.2% of the world’s total area under cultivation (Stock Exchange of Rosario, Argentina). Despite the intensity of this agricultural activity, data on pesticide pollution in surface water are rather scarce. In this sense, the aim of this work is to determine the presence of pesticides in surface water of four agricultural sub-basins of Argentine. An environmental monitoring was carried out to determine the impact of twenty-nine pesticides used in agricultural activities on the surface water quality of agricultural areas within the San Vicente, Azul, Buenos Aires southeast and Mista stream sub-basins. The samples were analyzed by solid-phase extraction (SPE) using OASIS HLB 60 mg cartridges and ultra-high-pressure liquid chromatography coupled to tandem mass spectrometry (UHPLC/MSMS) that provided good analytical quality parameters. The southeast of Buenos Aires was the site with the highest frequency of pesticides detection, followed by Azul and San Vicente microbasins. The most detected pesticides, considering all surface water samples, were atrazine, tebuconazole and diethyltoluamide with maximum concentration levels of 1.4, 0.035, and 0.701 μg L−1, respectively. The results obtained for all basins studied show the presence of residual pesticides in surface waters according the different agricultural activities developed.